Improving of Students’ Reading Comprehension using Cooperative Integrated Reading and Composition (CIRC) Method at Politeknik Ganesha Medan - Afri, Evan; Fithriani, Rahmah; Pardi, Pardi (International Journal of English and Applied Linguistics (IJEAL), 2026)
This study aims to determine whether the cooperative integrated reading and composition (CIRC) method has improved the reading comprehension of second-semester students at Politeknik Ganesha Medan. The researcher found that a lot of students at Politeknik Ganesha Medan had trouble reading the texts after talking to the English teacher and watching them. They can't figure out what the messages mean or what they mean. The researcher did this because she wanted to help the students with their reading comprehension problems. The researcher utilized the cooperative integrated reading and composition (CIRC) method to improve students' reading comprehension in response to the identified issue. The researcher utilized a pre-experimental design featuring a non-equivalent control group (Gay, 2006, p. 225). The group underwent a pre-test, treatment, and post-test. The research sample consisted of fifteen students. The researcher used only one type of tool, a reading test, to get information. A score will be given to each student's answer, and a formula will be used to find the average score. The scores on the posttest are higher than the scores on the pretest. Researchers could conclude that students' reading comprehension has been enhanced by utilizing the CIRC Method. One thing that helps students understand what they read better is the CIRC Method, which involves working together in groups to comprehend the material and answer questions about the stories. Some benefits of cooperative learning include positive interdependence, face-to-face interaction, individual accountability, and development of interpersonal and small group skills.